Terminology of State in the Quran On the Dimensions of Constitutional Law - Rohmah, Siti Ngainnur; Yunus, Nur Rohim (BULETIN ADALAH, 2024)
As the primary reservoir of Islamic doctrines, the Koran offers spiritual counsel and examines diverse facets of human existence, encompassing constitutional law. An essential aspect emphasised in the Koran is the vocabulary about the state or governance. This essay aims to elucidate the state language found in the Al-Quran and its significance in constitutional law. Additionally, it seeks to comprehend the ideas delineated in the Al-Quran concerning the organisation and operation of the state within the context of Islam. A profound comprehension of the specific vocabulary used in the Al-Quran about governance is crucial in establishing a solid conceptual basis for advancing Islamic constitutional law. This is particularly applicable in contemporary Muslim communities that require direction in establishing a government that aligns with Islamic ideals. The conclusion of the study indicates that the Al-Quran use the terms "Dawlah", "Daulah", and "Imarah" to emphasise the notion of state or leadership within the context of Islam. These two phrases highlight the significance of God's supremacy and fairness in governance. Through a comprehensive comprehension of this concept, Muslim communities can construct a nation founded upon authentic Islamic principles.